Prevalence of aphthous stomatitis reported in a private dental institution - a retrospective study - DHANVANTH. M,; MAHESWARI. T. N, UMA; RAJENDRAN, DEEPIKA (The journal of contemporary issues in business and government, 2020)
Aphthous ulcers or recurrent aphthous stomatitis (RAS) are benign ulcerated lesions common in oral mucosa with uncertain etiology, considered as immunologically mediated hence management of recurrence becomes challenging .The aim of the study was to assess the prevalence of various clinical types of Aphthous stomatitis reported in Oral Medicine Department of Saveetha Dental College. A total of 44 cases were collected from the Oral Medicine Department of Saveetha Dental College. The incomplete documented cases were not included. Statistical tests were used to calculate the frequency of age, gender, type of Aphthous ulcer and site of aphthous ulcer. The Pearson chi square test was used and analyzed in SPSS version 26. The comparison of frequency of age showed that aphthous ulcer was common in 20 to 35 years of age. On analysis of frequency distribution of Aphthousstomatitis males were higher [68%] than females [32%]. On comparing the clinical types of Aphthous ulcer , minor aphthous ulcer [79.5%] was higher than major aphthous ulcer [13.6%] and Herpetiform ulcer [6.8%] was least prevalent.On comparing the various site of Aphthous ulcer, tongue prevalence [36.6%] was higher. Pearson chi square association analysis of type of aphthous stomatitis with clinical site revealed statistical significance with p value <0.05.Minor aphthous ulcer more prevalent in tongue while major aphthous ulcer in labial mucosa and herpetiform in buccal mucosa.